Parasites and Planetary Systems: Towards an Eighteenth-Century Ecology? - Bezilla, Charlee (Lumen, 2024)
As eighteenth-century naturalists sought to determine the nature and origins of biological lifeforms, from polyps to primates to people, novelists extrapolated their ideas to other biospheres to imagine how life might develop under differing circumstances and propose their own “systems.” This paper examines two late-eighteenth-century texts that promote a hylozoic cosmogony, in which all matter is animate and life arises from celestial bodies, cycling down to animals, plants, and minerals. These two texts, Nicolas-Edme Rétif de la Bretonne’s proto-science-fiction epistolary novel Les Posthumes (1796-1802) and François-Félix Nogaret’s dialogue La Terre est un animal (1795), both describe humans, and all other life, as “parasites.” By analyzing these texts through the lens of the philosopher Michel Serres’s concept of parasitism, this paper argues that conceiving of people as parasites can provoke an ecological orientation that decenters the human and brings into relief humans’ relationality with and dependency on other lifeforms.